A photoswitchable “host-guest” approach for the selective enrichment of dimethoatefrom olive oil - Garcia, Raquel (2019)
This work describes the development of a new selective photocontrollable molecularly imprinted-based sorbent for the selective enrichment/pre-concentration of dimethoate from spiked olive oil samples. To achieve this goal an improved molecularly imprinted strategy relying on the embedding of a functional monomer containing an azobenzene chromophore as light-responsive element, on the crosslinked tridimensional molecular imprinted network, has been assessed. To address the mechanisms underlying template recognition and uptake/release of the analyte from the functional imprinted material, computational studies using a quantum chemical approach, have been explored. This new functional sorbent provides a straightforward controllable uptake/release of the target template using light as the stimuli tool, which is highly advantageous due to light manipulation characteristics, such as superior clean, precision and remote controllable properties. In general, this work will contribute to the imple- mentation of a photoswitchable analytical methodology that proves to be suitable for the selective isolation and further quantiﬁcation of dimethoate from olive oil matrices at levels similar to the maximum residues limits imposed by the legislation. The limits of detection, calculated based on 3 s ,was 1.6 mgL and the limit of quantiﬁcation, based on 10 s , was 5.2 mgL . The implemented sample preparation shows high reproducibility and recoveries (93.3 ± 0.4%